Dynamic machine model in complex plane - SANTOS, Francisco Costa (2024)
The present work implements a dynamic classical model of machines on complex plane. For this goal, the state equations for the machine angle, and for the machine rotor speed, , will be developed in complex domain. Moreover, the performance of the classical model of machines on complex plane are compared with its counterpart formulated in the real domain. The proposal is evaluated by using the well known test systems IEEE-9 bus and IEEE-39 bus. Additionally, a brazilian well used dynamics power system program named ORGANON is taken as benchmark for the studied cases. The analysis of the obtained results through the SIMULINK allow to demonstrate the computational advantage of the model in complex plane as the size of the system becomes larger.